The use of Fungus as CO2 Sequestration: A Systematic Review - MOHAMAD PAUZI, AMAR AIMAN; Juki, Prof. Ir. Ts. Dr. Mohd Irwan (Recent Trends in Civil Engineering and Built Environment, 2021)
Concrete is one of the important materials used in construction industry to construct a building, bridge, and many other structures. Despite of its advantage in compressive strength, concrete also has its own disadvantage, namely that concrete is a material that easy to crack due to several factors such as overload or the environment of the concrete itself. In addition, the manufacturing of concrete has brought a negative impact on the environment due to the emission of large amounts of carbon dioxide into the earth’s atmosphere due to the production of cement in the factory. Previous study shows that carbon dioxide sequestration in concrete can be done by mixing the capture carbon dioxide into concrete mixture during or before curing process. Another research found that the amount of carbon dioxide can be capture or sequestrate by using fungus and transform into mineral through a bio mineralization process, where mineral such as calcium carbonate (CaCO3) is precipitate in a condition where there is a presence of calcite in the environment. This study focused on effect of fungus on carbon dioxide sequestration in bio-concrete and also identified the factor affecting the rate of carbon dioxide sequestration in bio-concrete by using fungus as an added material by doing a systematic review. Data is selected from the eligible article and qualitative analysis is conducted to achieve the objective. Result of this research found that the effect of fungus in CO2 sequestration bring positive feedback to the rate of CaCO3 precipitation in bio-concrete and the factor affecting the rate of CO2 sequestration in bio concrete using fungus is due to the concentration of carbon dioxide and also surface area of fungus used.